ISO STANDARDS FOR AIR SYSTEMS - Guda, Viswanatha Reddy (Innovare Journal of Sciences, 2015)
Air systemÂ is a system of mechanical refrigeration in which cold air is compressed, cooled, and permitted to expand and thus acts as the refrigerating agent. International Standards bring technological, economic and social benefits. This article provides an introduction to the ISO 8573 and ISO 12500 series of International Standards which cover compressed air purity and test methods, as well as the purification equipment essential to achieve the standards. The amount of water present in a compressed air system is staggering. Combination of a small 2.8 m3/min (100 scfm) compressor and refrigeration dryer, operating for 4000 hours in typical Northern European climatic conditions can produce approximately 10,000 litres or 2,200 gallons of liquid condensate per year. If the compressor is oil lubricated with a typical 2 mg/m3 (2ppm) oil carryover, then though the resulting condensate would visually resemble oil, oil would in fact account for less than 0.1% of the overall volume and it is this resemblance to oil to which a false association is made. Testing standards are being revised to give the users an unblemished picture of how components will perform. These standards are being written to help users manage their total energy consumption. In order to help users evaluate their compressed air systems, additional standards are about to release and these newer standards can have significant impact on plant energy consumption if properly applied.